2019
DOI: 10.1080/13562517.2019.1696300
|View full text |Cite
|
Sign up to set email alerts
|

How international students of colour become Black: a story of whiteness in English higher education

Abstract: How international students of colour become Black: a story of whiteness in English higher education This article highlights how international students of colour are racialised in English higher education. Key performance indicators of racial inequality in the sector like achievement outcomes currently discount experiences of international students of colour. This is problematic as international students, as found in this study, identify themselves under the sector racial category of Black and minority ethnic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Although international students are often considered profitable to American institutions of higher education as their elevated tuition dollars contribute to the financial well-being of programs, Cantwell (2015) found that tuition-paying international doctoral students rather than undergraduate or master's students are mainly responsible for generating additional revenue for some public universities in the United States. Madriaga and McCaig (2022) opine that international students of color may experience racism, judgment regarding their language proficiency or accent, and unfair perceived cultural deficits -as though their cultural norms, though different, are inherently inferior.…”
Section: International Bipoc Doctoral Studentsmentioning
confidence: 99%
“…Although international students are often considered profitable to American institutions of higher education as their elevated tuition dollars contribute to the financial well-being of programs, Cantwell (2015) found that tuition-paying international doctoral students rather than undergraduate or master's students are mainly responsible for generating additional revenue for some public universities in the United States. Madriaga and McCaig (2022) opine that international students of color may experience racism, judgment regarding their language proficiency or accent, and unfair perceived cultural deficits -as though their cultural norms, though different, are inherently inferior.…”
Section: International Bipoc Doctoral Studentsmentioning
confidence: 99%
“…This study uses critical race theory (CRT), which focuses on the effects of "race" and racism on the lived experiences of black people and ethnic minorities. Initially developed by critical legal scholars (Bell, 1992;Delgado & Stefancic, 2017;Matsuda, 1987), CRT has increasingly been utilized by educational researchers to foreground race and racism in studies that explore lived experiences of black students (Dixson et al, 2006;Doharty et al, 2021;Ladson-Billings & Tate, 2016;Madriaga & McCaig, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This means that international students' intersectional identities are often ignored, both in research and in practice, by assuming their noncitizen status is a meaningful marker of diversity that signifies a shared experience. Although the intersections of international students' experiences and other identity markers such as race (Bardhan & Zhang, 2017;Madriaga & McCaig, 2019) or gender (Song, 2020) have received more recent attention, these reflections remain limited, particularly in research about ODDE.…”
Section: Problematic Assumptions Of Binary Definitions More Broadlymentioning
confidence: 99%
“…For work with international students, this means a growing recognition of the ways that they may be stigmatized and unfairly depicted through deficits (Moosavi, 2021). There is also a growing recognition for social inequalities, such as how international students' experiences may be racialized (Madriaga & McCaig, 2019). Thus, the subfield is slowly shifting towards critical recognitions of existing barriers and the framing of international students as "epistemic equals" (Hayes, 2019) although Stein (2019) argues such approaches remain on the margins and require greater engagement.…”
Section: Understanding International Students' Experiencesmentioning
confidence: 99%